Answer:
<h2>73 - 11 equals 62. <em><u>
THE ANSWER IS 31.</u></em></h2><h2><em><u>
PLEASE ADD AS BRAINEST.</u></em></h2>
Step-by-step explanation:
x-3y=7 2x-6y=12
You can multiply -2 in the first equation like this.
x+6y=7
2x-6y=12
Now you can eliminate 6y and -6y so cross them out and do x-2 which is -1 and 7-12 which is -5 -1/-5 would be .2
<h3 />
Answer:
-1
Step-by-step explanation:
Yes, because the sum of any 2 sides of the triangle is greater than the value of the third side.
Answer:
10x + 5
Step-by-step explanation:
x = some number
10x = 10 multiplied by 'x'
10x+5 = five more than 10 multiplied by some number